Walking to the gallery: Sondra Perry's "It's in the game" in San Diego in five fragments. Issue 2 (3rd July 2018) - Cimini, Amy
ABSTRACT: For two weeks in October 2017, the San Diego gallery Helmuth Projects displayed Sondra Perry's installation IT'S IN THE GAME '17 Or Mirror Trick for Vitrine and Projection. In the installation, Perry meditates on her twin brother's involvement in the class action suit O'Bannon vs the NCAA in which college athletes challenges the NCAA sale their names, images and likeness (NILs) to the video game company EA without the players' consent. Perry excavates the conditions of visibility that structured the NCAA's application of the so-called amateurism in O'Bannon, confronting the game with contested concepts of love and histories of display value as their intersection materialised in different registers of analysis: the juridical, the political economic, the familial and the aesthetic. The hours I spent with Game were filled with double-takes and second-guesses as Perry's likenesses leapt between these registers, careening through the impossible inside of digital processes controlled by something or something they could never hope to see.